Comparative Analysis of the Education Systems of Uzbekistan and Turkey: Generalization of the Study Experience (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Education plays a crucial role in the modern world, and its development is one of the priorities in many countries. Building a highly effective and high-quality general education system will contribute to the progress of various fields of activity throughout the state. The purpose of the research in the article is to conduct a comparative analysis of the general education systems of Turkey and Uzbekistan; to identify strengths and weaknesses, principles of construction and functioning of these systems, as well as their common and various features. The article used research methods such as analysis (an analysis of each general education system of a particular country was carried out, a certain set of characteristic features and traits was identified).